2013
DOI: 10.1371/journal.pone.0083349
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA Damage via Augmented Oxidative Stress Regulates Endoplasmic Reticulum Stress and Autophagy: Crosstalk, Links and Signaling

Abstract: Saturated free fatty acids (FFAs) have been implicated in the increase of oxidative stress, mitochondrial dysfunction, endoplasmic reticulum (ER) stress, autophagy, and insulin resistance (IR) observed in skeletal muscle. Previously, we have shown that palmitate-induced mitochondrial DNA (mtDNA) damage triggers mitochondrial dysfunction, mitochondrial reactive oxygen species (mtROS) production, apoptosis and IR in L6 myotubes. The present study showed that mitochondrial overexpression of human 8-oxoguanine DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 22 publications
2
38
0
Order By: Relevance
“…The mitochondrial pathway is one of the most important apoptosis signaling pathways in cells, and the Bcl 2 family is a key regulator of this pathway [28,49]. Bcl 2 functions as an anti-apoptotic factor in the outer mitochondrial membrane to maintain the integrity of the membrane, whereas Bax plays its pro-apoptotic role by disrupting the mitochondrial membrane.…”
Section: Discussionmentioning
confidence: 99%
“…The mitochondrial pathway is one of the most important apoptosis signaling pathways in cells, and the Bcl 2 family is a key regulator of this pathway [28,49]. Bcl 2 functions as an anti-apoptotic factor in the outer mitochondrial membrane to maintain the integrity of the membrane, whereas Bax plays its pro-apoptotic role by disrupting the mitochondrial membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Because mitochondrial dysfunction has been associated with IR, palmitate-induced alterations of mitochondria may explain why reducing ER stress was not effective for improving insulin signalling in myotubes. Furthermore, recent data have suggested that mitochondrial DNA damage is upstream of palmitate-induced ER stress and autophagy in L6 skeletal muscle cells [61], and that palmitate-induced oxidative stress contributed to the loss of insulin-stimulated phoshorylation of PKB [60]. Moreover, palmitate can be incorporated in ER phospholipid membranes, leading to modifications of ER morphology [56] that could contribute to altered insulin sensitivity [51].…”
Section: Er Stress and Skeletal Muscle Insulin Resistancementioning
confidence: 99%
“…However, other studies point out that ER alterations are subsequent to mitochondrial dysfunction in metabolic diseases. For example, it was shown that changes in ER homoeostasis occurred via a mitochondria-dependent pathway in the liver of rats exposed to excessive inflammation [68] and in palmitatetreated L6 myotubes [61].…”
Section: Interrelationship Of Mitochondrial Dysfunction and Er Stressmentioning
confidence: 99%
“…16 Our previous study found that ROS contributed to aldosterone-induced podocyte injury. 17 Recently, oxidative stress has been shown to be an initiator and major contributor to both ER stress and autophagy, 18 although the underlying mechanisms responsible for these events are still unknown.…”
mentioning
confidence: 99%